Analysis on air craft winglet at different angles by using CFD simulation. (2022) - Seshaiah, T.; Vasu, B.; Kumar Reddy, K.Vijaya; Bridjesh, P.
Abstract: In this paper, the primary emphasis was on the modelling and study of aircraft winglets. Drag mitigation is a major problem in aerodynamic engineering. A gadget called a winglet is mounted vertically at a series of angles on the end of the aircraft wing to minimise drag. By decreasing the aircraft drag, the winglet configuration would decrease the fuel consumption and making the aircraft more stable during takeoff, as well as giving the aircraft engine a longer life by reducing the load on the engine thrust. The aim is to design and simulate a using CATIA V5, which is used to build the various winglet models (blended winglet, rated winglet) at different winglet angles (35 0, 65 0 and 90 0 ) with angle of attack and ANSYS is used to measure and simulate the winglet model. In this study it was observed that wings with winglets produce higher lift force/Drag for the CFD and its static FE analysis study. Its effectiveness is reduced by a certain degree of angle of attack and by rising further to a higher angle of attack. A potential solution for enhancing the aerodynamic performance of an aircraft seems to be the examined idea of variable angle winglets.